Acardian and headless fetus: Twin reversed arterial perfusion sequence. A case report - Gavidia Núñez, Reynaldo (2022)
The reverse arterial perfusion sequence is a complication of monochorionic twin pregnancy, occurring in 1 in 35,000. In this anomaly, artery-artery vascular anastomoses occur in the placental bed, forming a pump twin with high arterial perfusion pressure and a completely aardic recipient twin. Mortality is probably from heart failure and anemia that occurs early in pregnancy. We present a case of acardiac and headless fetus in a twin pregnancy in a 22- year-old patient, the product of a 36-week-one-day biamnitic monochorial twin gestation, attended the emergency room due to loss of amniotic fluid and absence of cardiac activity in a twin. Prenatal diagnosis of reverse arterial perfusion sequence in twins is essential to improve prognosis.